Local Government and Traditional Authorities in Concert: Towards a More Productive Relationship - Callistus Mahama (Commonwealth Journal of Local Governance, 2009)
Ghana embarked on decentralisation in 1988 as a way of bringing decision making closer to the people. Since then, there have several reforms with a view to strengthening local governance. This article identifies a major challenge still facing Ghana’s decentralisation: Partnership between local government and traditional authorities. The paper discusses the fuzzy relationship between local governments and traditional authorities as a result of constitutional and legislative ambiguity on their relationship. Traditional Authorities perform important functions in the country, albeit their roles have waned since independence. Yet current legal provisions on local government have not sufficiently clarified their role in local administration. This has led to a murky and competing relationship between traditional authorities and local governments. In localities where mutual relationship exists, it is mainly as a result of the personalities involved and this has had a positive effect on the development of the area. The paper concludes by advocating for measures which among others include a re-enactment of legislation which will define the working relationship between traditional authorities and local government.